2018
DOI: 10.18203/2349-3933.ijam20181068
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of patients presenting with acute myocardial infarction

Abstract: Background: Cardiovascular diseases are the number one cause of death globally. Cardiovascular diseases have emerged as a major health burden in developing countries. Myocardial infarction (MI) is defined by the demonstration of myocardial cell necrosis due to significant and sustained ischaemia. Author attempted to study the risk factors and clinical profile of patients with MI admitted in Cardiology Department of tertiary care center, Chitwan, Nepal.Methods: This descriptive retrospective study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
5
10
1
3
Order By: Relevance
“…Th e most common presenting symptom was chest pain, followed by shortness of breath. Th is fi nding is consistent with another study done in 2018, which also reported chest pain (86.36%) and shortness of breath (42.42%) to be the two most common symptoms in MI patients [29] . Seetharama et al [27] reported sweating with chest pain to be the most common symptom in their sample; the other common symptoms in their study were breathlessness, giddiness, palpitations, and vomiting.…”
Section: Figuresupporting
confidence: 91%
“…Th e most common presenting symptom was chest pain, followed by shortness of breath. Th is fi nding is consistent with another study done in 2018, which also reported chest pain (86.36%) and shortness of breath (42.42%) to be the two most common symptoms in MI patients [29] . Seetharama et al [27] reported sweating with chest pain to be the most common symptom in their sample; the other common symptoms in their study were breathlessness, giddiness, palpitations, and vomiting.…”
Section: Figuresupporting
confidence: 91%
“…Similarities were found in the literature regarding the profile of the interviewed population, with a higher prevalence of males in patients affected by AMI. [13][14][15][16][17] In addition, it was found that most of these patients had hypertension as a risk factor for the cardiovascular event [13][14][15][16] . Regarding smoking, less than half of the population interviewed had this addiction, as also found in other publications.…”
Section: Discussionmentioning
confidence: 99%
“…The differences were statistically significant. In Adhikari et al 20 study most of the patients (90.15%) had STEMI. Our findings correlate well with those of the above authors.…”
Section: Ecg Findingsmentioning
confidence: 92%
“…Ambali et al 22 observed that a total of 60 (40%) patients had addictive habits, the most common habit noted was smoking and was present in 29 (19.3%) patients, followed by tobacco chewing in 18 (12%) patients. Adhikari et al 20 observed tobacco smoking/chewing (62.87%) as a major risk factor contributing to myocardial infarction. Hypertension (43.18%) was the second most common risk factor followed by diabetes mellitus (34.09%) and dyslipidaemia (21.21%).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation